2020
DOI: 10.3390/agriculture10050165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Sowing Red Light Treatment of Sweet Corn Seeds on the Quality and Quantity of Yield

Abstract: This paper presents the results of a study on the effects of red light treatment of sweet corn seeds on the quantity and quality of the subsequent yield (total and marketable), as well as the length of cobs and thousand kernel weight. The respective groups of kernels were exposed to light: 1—once (K1), 2—twice (K2), and 3—thrice (K3); the control seeds were untreated. The light treatment had a positive impact on the analyzed values. Relative to the control, we observed a yield increase of approx. 5% for the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…While previous studies have evaluated the effects of maize seedling performance in outdoor environments using various sources and intensity of lasers ( Samuilov & Garifullina, 2007 ; Hernández-Aguilar et al, 2011; Srećković et al, 2014 ; Hasan et al, 2020a ; Hasan et al, 2020b ; Dziwulska-Hunek, Szymanek & Stadnik, 2020 ), few have reported physiological responses by using laser under these conditions ( Asghar et al, 2016 ; Rózanowski et al, 2020 ). With increased understanding of these responses, production in controlled environments can be more effectively optimized.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have evaluated the effects of maize seedling performance in outdoor environments using various sources and intensity of lasers ( Samuilov & Garifullina, 2007 ; Hernández-Aguilar et al, 2011; Srećković et al, 2014 ; Hasan et al, 2020a ; Hasan et al, 2020b ; Dziwulska-Hunek, Szymanek & Stadnik, 2020 ), few have reported physiological responses by using laser under these conditions ( Asghar et al, 2016 ; Rózanowski et al, 2020 ). With increased understanding of these responses, production in controlled environments can be more effectively optimized.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change remains prevalent in the delineated region, presenting a range of challenges for smallholder livestock farmers (SLF) in Sub-Saharan Africa. Various changes in temperature, the mountainous and arid landscape and water availability impact on the pastures and forage quantities and quality [20], feed-grain pricing, and disease and pest distributions in rural settings.…”
Section: Livestock Evolution-a Focus On Risksmentioning
confidence: 99%
“…Therefore, improving the phytochemical contents in Brassica plants and their sprouts to boost their nutritional and health-promoting effects has arisen many concerns. In this regard, several plant growth and/or bioactivity-promoting techniques have been widely applied, on the basis of the positive impacts of some environmental stressors and elicitors on the production of bioactive secondary metabolites in sprouts. , For instance, magnetic field and laser irradiation have recently been used for increasing plant nutritive value and productivity . According to their uses and applications, laser light is categorized into two types, pulsed and continued lasers.…”
Section: Introductionmentioning
confidence: 99%